The role of financing sources in achieving local development A field study in the municipality of El-Euch - Bordj Bou Arerridj- - Lakhal , Said (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
This study dealt with the topic of the role of funding sources in achieving local development , q field study in the municipality of El–Euch- Bordj Bou Arreridj- Where this study aims to reveal the municipality funding from the different sources, Whether in the value of the amounts allocated to finance local development or its sours and its role in raising the level of local development and Whether it is sufficient in achieving the aspirations of the citizen in this region, and We have also adopted the descriptive analytical approach and some tools for collecting field material such as simple observation and free interview , as Well as the research sample that Was randomly selected from the original community for research , and accordingly a set of questins Wer formulated about funding from government sources as Well as taxes the internal municipality and the contribution of all this to the achievement of local development , and through these question , We formulated the research hypotheses on the grounds that development is the main element for stability and advancement in various field , so it takes various forms aimed at advancing the human element towards development , prosperity , prosperity and stability in line With its needs and capabilities . the economic and social municipality and in order to achieve local development , the municipality of El Euch needs the field of study to self-financing such as taxes related to the various activities of merchants , craftsmen and productive institutions in the municipality However, these incomes do not cover the needs to ensure effective and harmonious local development . As a result , the government established two additional sources of financing for development in the municipalities , namely , the municipal plans for development as Well as the solidarity and Guarantee fund among the municipalities the study has two sides ; A theoretical aspect and a field one , the first was to talk about local development and its sources of financing , and the second was to study the effectiveness of the three funds in achieving development in the municipality , the field of study , to reach in the end research results , the most important of which was that the large part that contributes to the development of the municipality is through the solidarity and Guarantee fund for group while the municipality’s revenues from the management and equipment department cannot sufficiently contribute of the municipality .